Creativity, diversification and learning processes in local economies - Vecchiatti, Karin (Organicom, 2015)
This essay presents the idea that the creative professions show the possibility of contributing to a locality, inasmuch as toa large extent they present flexibility and agility in the economic diversification while sponsoring its development duringapprenticeship, which for the management of people and enterprises becomes a decisive factor. The text shows examplesof various initiatives, presents a theoretical approach based on development, relying also on contributions of the closenessbetween human sciences and natural sciences.